Penerapan Teknologi Nanofluida pada Hand washer dalam Upaya Pencegahan Penyebaran Covid-19 di Desa Tanjung Bungin Kab. Karawang - Vera Pangni Fahriani; Sutrisno Sutrisno; Apid Hapid Maksum; Marchanda Rahmawati Martin; Reza Setiawan (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This Community Service Program (PKM) aims to assist and carry out outreach as an effort to prevent the spread of Covid-19 in a standard and effective manner, and to help cultivate a culture of mutual cooperation and Village independence in making nanofluid droplet hand washer fluid technology. The partner for this service activity is Tanjung Bungin Village, Karawang. The village's location close to Tanjungpakis Beach means that many people pass by and stop by, but there is still low awareness of the Covid-19 pandemic and there are no adequate public facilities for nanofluid droplet hand washer technology and there has not yet been a good awareness of cultivating mutual cooperation and village independence in making nanofluid droplet hand washer technology is a problem. The solution to this problem is to apply nanofluid technology to hand washers. The PKM implementation method is carried out from the preparation stage to the use of hand washer tools and materials directly in public facilities as well as evaluation by looking at and listening to suggestions for tools and materials for improvement. The results of this PKM were in the form of natural hand washer fluid and nanofluid hand washer tools as well as a positive response to socialization activities and handover of hand washer tools.